2011
DOI: 10.1016/j.jvs.2010.11.121
|View full text |Cite
|
Sign up to set email alerts
|

The role of carotid plaque echogenicity in baroreflex sensitivity

Abstract: These findings suggest that echogenic plaques are associated with reduced baroreflex function compared with echolucent ones. Further investigation is warranted to define whether such an sBRS impairment could be responsible for cardiovascular morbidity associated with echogenic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…8,10,12,17,24,26,33 Echogenic atherosclerotic plaques are associated with reduced CSB sensitivity in comparison to echolucent ones. 59 Moreover, heavily calcified plaques not only require higher pressures for dilation, but they also more efficiently transmit these pressures to the carotid wall and to the CSBs. 8,18 Recent studies have suggested that patients with a small total plaque volume measured on computed tomography and fibrous tissue accounting for .60% of plaque volume on intravascular ultrasound virtual histology are more likely to develop HI.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,12,17,24,26,33 Echogenic atherosclerotic plaques are associated with reduced CSB sensitivity in comparison to echolucent ones. 59 Moreover, heavily calcified plaques not only require higher pressures for dilation, but they also more efficiently transmit these pressures to the carotid wall and to the CSBs. 8,18 Recent studies have suggested that patients with a small total plaque volume measured on computed tomography and fibrous tissue accounting for .60% of plaque volume on intravascular ultrasound virtual histology are more likely to develop HI.…”
Section: Discussionmentioning
confidence: 99%
“…Baroreflex sensitivity was found to be impaired in patients with bilateral carotid atherosclerosis (Nasr et al, 2005) or with echogenic plaques (Tsekouras et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, ABP was monitored noninvasively with photoplethysmography (Finapress 2300 -Ohmeda, The Netherlands). (14).…”
Section: Populationmentioning
confidence: 99%
“…Two other determinants of baroreflex diminution are age (5,12), and carotid atherosclerosis (13,6,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%